The Role of Home Gardens in Developing Cities for Improving Workers' Psychological Conditions - Samuel Nanda Lazuardi; Bambang Sulistyantara; Prita Indah Pratiwi (Journal of Contemporary Urban Affairs, 2022)
During the lockdown period, people were restricted from doing many things, particularly activities outside the home, putting strain on psychological circumstances. This study intends to demonstrate that providing a home garden to improve the psychological state of the workers' community may alleviate the challenges of access to green open space in city settings. This study investigates the psychological state of employees and the impact of home gardens on the psychological state of workers in numerous cities in Indonesia during the pandemic. The survey was carried out utilising the Snowball sampling approach by asking various questions and filling out a questionnaire on the participants' backgrounds and psychological problems using PSS-14 and WEMWBS. Data from participants were analysed using correlation and ANOVA. According to the findings of this study, the presence of a home garden utilised for activities has a substantial impact on the psychological condition of the working community. It is advised that the workers' community participate in activities in the home garden five days a week for at least one hour. On the other hand, it is suggested that urban housing developers pay more attention to the house garden and its constituent aspects.